Aflatoxin M1 in samples of "minas" cheese commercialized in the city of Belo Horizonte - Minas Gerais/Brazil - PRADO,Guilherme (2000)
Milk products such as cheeses may be contaminated by aflatoxin M1 when dairy cattle have consumed feeds contaminated with aflatoxin B1. Samples of "Minas" cheeses (fresh, canastra and standard) were collected by the Inspection Service in the Mercado Central in Belo Horizonte city, Minas Gerais - Brazil. A purified extract was obtained by extraction with dichloromethane followed by a washing with n-hexane and immunoaffinity column purification. The quantification of aflatoxin M1 was done by high performance liquid chromatography (HPLC) using a fluorescence detector. Recoveries were about 75%. In 56 of the 75 samples (74.7%), the presence of aflatoxin M1 was detected in concentrations ranging between 0.02 and 6.92ng/g of cheese. In the positive cases ( > or = 0.02ng/g) the mean contamination level of aflatoxin M1 was 0.08ng/g in fresh cheese, 0.36ng/g in canastra cheese and 0.62ng/g in standard cheese. No aflatoxin M1 maximum tolerance level in cheese has been established in Brazil.